Women's magazines, crime, and justice: invitational rhetoric in a decade of true crime in Australian Women's Weekly - Pâquet, Lili (True crime and women, 2025)
This chapter examines the intersections of justice, feminism, and popular culture represented by true crime stories in women’s magazines. It analyses true crime stories that appeared in Australia’s longest-running and consistently popular women’s magazine, Australian Women’s Weekly, over ten years of publication from 2010 to 2019. The chapter answers two questions: what types of stories and themes recur in the magazine’s true crime content, and how does the magazine shape perceptions of justice? The analysis uncovered four common story types in the true crime content: those highlighting institutional failure toward women; those appealing to a community of female readers for help; those seeking to educate a community of women to prevent crime before it happens; and those celebrating the trailblazing women making change to the justice institutions from within. Australian Women’s Weekly shaped perceptions of justice in these true crime stories using invitational rhetoric, which Foss and Griffin (1995) define as the offering of different perspectives in order to come to mutual understanding of an issue.